PHONOLOGICAL CHALLENGES IN INDONESIAN SYLLABIFICATION: INSIGHT FROM KOREAN LEARNERS - Kurniati, Nur Utami Sari'at; Koh, Young Hun; Kim, Dong Hoon (Universitas Islam Sumatera Utara (UISU), 2024)
This study is aimed at finding out how the differences in sound inventory and syllable structures between Indonesian and Korean influence the phoneme realization of Korean learners studying Indonesian. It involves 14 Korean learners and data for this study was obtained through documentation. The syllabification analysis showed that there were several processes occurring in speech production, such as simplification of the syllable structure, the addition and deletion of sound, and the change of sound segments. The simplification of the syllable was shown in the pronunciation of the consonant cluster, which was pronounced as two separate syllables. The addition of sound was obvious in some words, which was observable at the final position of the first syllable. The deletion of sound was found in the word ending in /r/, in which the sound was dropped. The sound change was overtly seen in the pronunciation of consonants /v/ and /r/. These processes might result from the different sound inventory and syllable structures between Korean and Indonesian. Some of those issues need to be addressed significantly since phonological errors might seriously interfere with understanding.